What's past is prologue: Recalled parenting styles are associated with childhood cancer survivors' mental health outcomes more than 25 years after diagnosis. (May 2020) - Ernst, Mareike; Brähler, Elmar; Klein, Eva M.; Jünger, Claus; Wild, Philipp S.; Faber, Jörg; Schneider, Astrid; Beutel, Manfred E.
Abstract: Background: With the increased survival rates of childhood cancer, long-term survivors' well-being over the life span has come into focus. A better understanding of the determinants of childhood cancer survivors' (CCS) mental health outcomes contributes to the identification of vulnerable individuals as well as to the development of evidence-based prevention and intervention efforts. It has been noted that psychosocial factors such as parental rearing behavior shape individual differences in mental health. There is also evidence that parents show altered parenting behavior in the face of childhood cancer, e. g. that they express more emotional support, but also more worries. However, little is known about the relevance of different parenting styles for CCS′ mental health decades after diagnosis and treatment. Methods: We examined the associations of recalled parenting styles and disease-related factors with lifetime diagnoses of depression and anxiety disorders in a German, registry-based sample of adult CCS (N = 948, 44.50% women) with survival times >25 years. We conducted logistic regression analyses of lifetime diagnoses of depression and anxiety disorders, respectively, on dimensions of recalled parental rearing behavior (measured with a validated German short version of the EMBU) controlling for relevant adjustment variables such as the presence of physical illnesses. Results: Recalled parenting styles of both parents had statistically relevant associations with CCS′ lifetime depression and anxiety diagnoses. Maternal emotional warmth was related to fewer lifetime diagnoses of depression and fewer lifetime diagnoses of anxiety. Memories of paternal control and overprotection were positively associated with lifetime diagnoses of anxiety. Conclusion: The results indicate that mental representations of one's caregivers are associated with psychological long-term outcomes. Thus, medical professionals should involve the parents and support them in accompanying their child through the difficult times of treatment and survivorship. Interventions aimed at fostering survivors' quality of life should consider the sustained relevance of early relationships. Highlights: We studied determinants of long-term childhood cancer survivors' mental health. Survivors' outcomes were associated with mental representations of their parents. Maternal emotional warmth lowered the risk of depression and anxiety diagnoses. Paternal overprotection/control elevated the risk of lifetime anxiety diagnoses. Memories of earliest relationships could inform prevention and intervention efforts.